Amphibia, anura, bufonidae, Rhaebo ecuadorensis mueses-cisneros, cisneros-heredia & McDiarmid, 2012, and anura, hylidae, Phyllomedusa tarsius (cope, 1868): Range extensions and first records for Zamora-Chinchipe province, Ecuador - Ordoñez Delgado, L. (2016)
We report the first provincial records for Rhaebo ecuadorensis Mueses-Cisneros, Cisneros-Heredia & McDiarmid, 2012, and Phyllomedusa tarsius (Cope, 1868) in Zamora-Chinchipe, southern Ecuador. The new locations are significant because they represent the southernmost records in Ecuador as well as the westernmost limits of the ranges of these two species. © 2016 Check List and Authors.